Indications and criteria for evaluation of competence maturity of bachelors in the specialty 51.03.02 “folk artistic culture” (in the context of federal state educational standards (fses) 3+) - Olga P. Karnikova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Renewal of professional education system sets new requirements for evaluation of the educational outcome. Due to introduction of the new educational standards projects, there is a need to analyze changes brought by these projects. This article covers review of the educational standards for professional education of bachelors in the specialty 53.03.02 “Folk Artistic Culture”. The primary goal of this article is to review changes made in the FSES 3+ educational process. This paper discloses indications and criteria for evaluation of maturity of general professional and professional competencies to perform certification of the course “Theory and methods of ethno-cultural education”. The material presented in this article may help teachers in updating of educational programs in the context of next- generation standards implementation.